Vertiscaping – edges of tomorrow - Patel, M A; B, Kapadiya D; Chawla, S L; Shah, H P; Singh, Alka (Indian Horticulture, 2019)
The concept of vertiscaping dates back to 600 BC with the hanging gardens of Babylon which is one of the seven wonders of ancient world. Green architecture has become a popular topic in discussions concerning environmental sustainability, especially in urban areas. Green walls or vertiscaping present an interesting opportunity as they are able to fill an underutilized portion of the urban fabric. The integration of the living, organic systems characterized by green walls and green roofs, with the inorganic and lifeless structures that have come to dominate modern architecture, holds the promise of a new type of ‘living’ architecture.